Pharmacokinetics and Safety of Glasdegib in Participants With Moderate/Severe Hepatic Impairment: A Phase I, Single‐Dose, Matched Case‐Control Study. Issue 7 (23rd December 2020) - Masters, Joanna C.; LaBadie, Robert R.; Salageanu, Joanne; Li, Jerry; Shaik, Naveed
Abstract: This phase I open‐label trial (NCT03627754) assessed glasdegib pharmacokinetics and safety in otherwise healthy participants with moderate (Child‐Pugh B) or severe (Child‐Pugh C) hepatic impairment. Participants with hepatic impairment and age/weight‐matched controls with normal hepatic function received a single oral 100‐mg glasdegib dose under fasted conditions. The primary end points were area under the plasma concentration–time curve from time zero to infinity (AUCinf ) and maximum plasma concentration (Cmax ). Twenty‐four participants (8/cohort) were enrolled. Glasdegib plasma exposures in moderate hepatic impairment were similar to controls, with adjusted geometric mean ratios (GMRs) of 110.8% (90% confidence interval [CI], 78.0–157.3) for AUCinf and 94.8% (69.9–128.4) for Cmax versus controls. In severe hepatic impairment, glasdegib plasma exposures were lower than controls (AUCinf GMR, 75.7%; 90%CI, 51.5–111.0; Cmax GMR, 58.0%; 90%CI, 37.8–89.0). Unbound glasdegib exposures were similar to controls for moderate (AUCinf, u GMR, 118.1%; 90%CI, 88.7–157.2; Cmax, u GMR, 101.1%; 90%CI, 78.4–130.3) and severe hepatic impairment (AUCinf, u GMR, 116.3%; 90%CI 81.8–165.5; Cmax, u GMR, 89.2%, 90%CI, 60.2–132.3). No treatment‐related adverse events or clinically significant changes in laboratory values, vital signs, or electrocardiograms were observed. Together with previous findings, this suggests glasdegib dose modifications are not required based on hepatic impairment.